Transit of solids through the human colon: regional quantification in the unprepared bowel - Proano, M; Camilleri, M; Phillips, S F; Brown, M L; Thomforde, G M (The American journal of physiology, 1990)
We used a noninvasive method to label the solid phase of contents in the unprepared human colon. 111In-labeled Amberlite pellets (0.5-1.8 mm diam) were placed in a gelatin capsule that was then coated with a pH-sensitive polymer (methacrylate). In vitro, the capsules disintegrated in simulated small bowel contents within 1-2 h; when ingested by healthy subjects, capsules released radiolabel in the distal ileum or proximal colon in 13 of 15 subjects. Transit of 111In-pellets through the unprepared colon could then be quantitated radioscintigraphically. Segmental transit was defined in the ascending (AC), transverse (TC), descending (DC), and rectosigmoid (RS) colon. Radioactivity was also quantitated in stools. At 12 h, radioactivity was most obvious in the AC (59 +/- 11%, mean +/- SE) and the TC (21 +/- 6%); at 24 h, counts were distributed equally between AC, TC, and stools (P greater than 0.05); by 48 h, 56 +/- 11% counts had been excreted, although 30 +/- 10% remained in the TC. At 24 and 48 h, the amount in DC or RS was lower (P less than 0.05) than in the TC or in stools. Emptying of the AC was characterized by an initial lag period, when no counts emptied into the TC, followed by a period of emptying that was approximately linear. Thus this simple approach is able to label contents in the healthy human colon. The ascending and transverse colon appear to be sites of storage of solid residue, whereas the left colon and rectosigmoid function mainly as conduits.